Analisis Diksi dan Gaya Bahasa Dalam Puisi ‘UNTUKMU’ Karya Fiersa Besari - Nanda Suhendi; Bambang Hartanto (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
The title of this article is "Analysis of diction and language style in Fiersa Besari's poem 'For you'". The problems discussed in this research are diction and language style in Fiersa Besari's poetry. The aim of this research is to describe the diction and language style in Fiersa Besari's poetry. The advantage of this research is that teachers and students can understand the vocabulary and language style of poetry, and teachers can choose poetry as school material in accordance with its pedagogical effects. This research is a descriptive research. Data sources were obtained from data and documents collected in the form of primary data in the form of the poem 'Fiersa Besari Untukmu' and secondary data in the form of supporting books suitable for this research. This data analysis was carried out in several stages. This means studying literature through reading, noting, and identifying lines of poetry that contain the diction and language style of the poetry. The data analysis method used is descriptive. Data analysis concludes that there are denotative and connotative meanings in the diction and language style of poetry.